a)By completing the square, prove the quadratic formula starting from ax^2+bx+c=0, b) hence, or otherwise solve 3x^2 + 7x -2= 9, to 3s.f.

a)starting from ax2+bx+c=0, divide through by a, x2+(b/a)x+c/a=0, complete the square (x+(b/2a))2-(b/2a)2 +c/a=0, expand (x+(b/2a))2-(b2/4a2)+c/a=0, Combine fractions and rearrange,(x+(b/2a))2=(b2-4ac)/4a2, square root both sides, x+b/2a=±√(b2-4ac)/2a, minus b/2a from both sides and obtain quadratic formula of x=(-b±√(b2-4ac))/2a.
b)3x2 + 7x -2= 9, to use quadratic formula, equation must equal 0, 3x2 + 7x -11=0 , x=(-7±√(72-43-11))/2*3 =1.08 or -3.41 (3s.f.)

Answered by Yusuf H. Maths tutor

2962 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Please expand the following brackets: (x+3)(x+5). Give your answer in its simplest form.


There are n sweets in a bag. 6 of the sweets are orange. The rest of the sweets are yellow. Hannah takes a sweet from the bag and eats it. Hannah then takes at another sweet. The probability that Hannah eats two orange sweets is 1/3. Show that n²-n-90=0


Solve the simultaneous equations: (1) 4x + y = 7 and (2) x - 3y = 5


A straight line passes through the point (0, 6) and is perpendicular to y = 4x - 5. Find the equation of this line, giving your answer in the form y = mx + c .


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences